Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(x-2=-6\)
\(x=-6+2\)
\(x=-4\)
2) \(-5x-\left(-3\right)=13\)
\(-5x+3=13\)
\(-5x=13-3\)
\(-5x=10\)
\(x=-2\)
3) \(15-\left(x-7\right)=-21\)
\(15-x+7=-21\)
\(22-x=-21\)
\(x=22+21\)
\(x=43\)
b) \(2x-\left(-17\right)=15\)
\(2x+17=15\)
\(2x=15-17\)
\(2x=-2\)
\(x=-1\)
5) \(\left|x-3\right|-7=13\)
\(\left|x-3\right|=20\)
\(\Rightarrow\orbr{\begin{cases}x-3=20\\x-3=-20\end{cases}}\Rightarrow\orbr{\begin{cases}x=23\\x=-17\end{cases}}\)
1) x-2=-6
x=-6+2=-4
2)-5x-(-3)=13
-5x =13+(-3)=10
x=10:(-5)=-2
3) 15-(x-7)=-21
x-7=15-(-21)=36
x=7+36=43
4) 3x+17=2
3x=2-17=-15
x=-15:3=-5
1) x-2 = 6
<=> x = 6+2 =8
2) -5x-(-3)=13
<=> -5x+3 =13
<=> -5x=13-3=10
<=> x = 10:(-5)
<=> x=-2
3) 15-(x-7)=-21
<=> x-7 = 15 -(-21) =36
<=> x = 36 +7 = 43
4) 3x+17 = 2
<=> 3x = 2-17 =-15
<=> x=-15 :3 = -5
-5x -(-3) = 13
-5x + 3 = 13
-5x = 13 - 3
-5x = 10
x = 10 : (-5)
x = -2
45 - (x - 9) = -35
45 - x + 9 = -35
45 - x = -35 - 9
45 - x =-44
x = 45 - (-44)
x = 89
15 - (x - 7) = -21
15 - x + 7 = -21
15 - x = -21 - 7
15 - x = -28
x = 15 - (-28)
x = 43
(-5) + x = 15
x = 15 - (-5)
x= 20
13/15 - (13/21 + x) . 7/12 = 7/10
=> (13/21 + x). 7/12 = 13/15 - 7/10
=> (13/21 + x) . 7/12 = 1/6
=> 13/21 + x = 1/6 : 7/12
=> 13/21 + x = 2/7
=> x = 2/7 - 13/21
=> x = -1/3
a)x-2=6-5x-16
6x= -8
x= -4/3
b)-5x-(-3)-x=13-x
-5x+3-x=13-x
-5x=10
x=-2
c)15-(x-7)=-21-x
15-x+7=-21-x
22=-21 ( vô lí)
x không có giá trị
D)3x+17=2+3x+15
17=17
x có vô số giá trị
e) x-45-(x-9)=-35-x
x-45-x+9=-35-x
-x=1
x=-1
f) -5+x=15-x-2x
4x=20
x=5
g) 2x-(-17) =15
2x+17=15
2x=-2
x=-1